Endomarketing, Service Quality and Management in the Education Sector - Linares Castillo, Oscar Marcelo (2022)
This paper offers an approach to endomarketing, service quality and mana- gement in the educational sector in our country. It explains the trends, strate- gies and context of endomarketing, then it articulates the concept of service quality and endomarketing in the context of the educational sector; it also provides an approach to internal marketing and its external impact on the ac- tivities carried out by educational institutions, finally its importance in educational management, in increasing resources and brand value, through the sense of belonging, motivation and incentives.